Penyandian File Gambar dengan Metode Substitusi dan Transposisi - Aji Supriyanto; Eka Ardhianto (Dinamik, 2008)
Cryptography is a science which studying about safety of messages, so it makes themessages cannot be read by unauthorized persons. Cryptography have two kinds of algorithmfirst is encryption algorithm, that is algorithm altering plaintext become the ciphertext, and thesecond is decryption algorithm that is algorithm altering ciphertext become the plaintext,  thatconducive of message can only be made and read by authorized persons. Plaintext represent themessage able to be read,  while ciphertext is message which have pass by the encryption process,so that order the ciphertext difficult to be translated or read. And method of substitution andtranspotition method are some of conventional technique able to be used to protect the picturesfiles, so that produce the pictures files which do not easy to to be read. The conventionaltechnique basically use a same key to do the encryption  and decryption process.